Rewriting the bereaved self: The role of narrative in rebuilding the self and constructing meaning following the loss of one’s spouse - Den Elzen, Katrin (Australiasian Association of Writing Programs, 2015)
Losing one’s spouse is one of the most difficult experiences we can face in life. It typically contests our sense of self, requiring the bereaved to rebuild the self. Narrative is well suited to facilitate identity reconstruction following grief. This paper posits that further research is needed into the specific narrative processes that facilitate recovery from grief in autobiographical writing. It intends to contribute to this gap in knowledge by linking bereavement theory with narrative theory in a textual analysis of the grief memoir To have and to hold (1997) by Walter Mikac, co-written by Lindsay Simpson. Through the close reading of To have and to hold and my own autobiographical writing this paper analyses the specific ways in which identity reconstruction takes place in the text, in particular narrative structure and metaphor. In accord with contemporary grief theory as espoused by Robert Neimeyer it argues for the importance of meaning making in the reconstruction of the self following bereavement, especially in the case of premature and sudden loss. In its analysis of Mikac’s meaning making in the text, it employs Neimeyer’s theory of meaning construction which posits that meaning can be found either in the life of the survivor or in the loss itself. Lastly, I draw observations about my personal experience as a postgraduate student writing a grief memoir and discuss how the symbiosis of being both author and academic researching bereavement has contributed to my own identity reconstruction.